Designing an Advanced Cash Transfer Program in the Palestinian Territories - Hillis, Samira; Leite, Phillippe; McDonald, Laura; Frost, Lillian (World Bank, Washington, DC, 2013)
The Palestinian Authority (PA)- administered Cash Transfer Program (CTP) is considered one of the most advanced cash assistance programs in the Middle East and North Africa (MENA) region. Using its sophisticated management information system (MIS), which includes a poverty-targeting database, it provides timely quarterly payments to beneficiary households using a uniform payment modality. The CTP was established, with support from the PA, after a merger between the World Bank-funded Social Safety Net Reform Project (SSNRP) and the European Union (EU)-funded Special Hardship Case (SHC) program in 2010. Since the CTP provided its first payment to households in the Palestinian Territories (PT) that year, the number of beneficiary households has increased by almost 59 percentage reaching almost 100,000 households.